Genetic variation and genetic distance of the Sakai tribe in Riau Province and the Minangkabau tribe in Pagaruyung Village, West Sumatra based on microsatellite DNA - Tyara, Tyara; Junitha, I Ketut; Wirasiti, Ni Nyoman (Jurnal Biologi Udayana; Vol 25 No 1 (2021): JURNAL BIOLOGI UDAYANA, 2021)
There are several versions can explain the origin of the Sakai tribe. Sakai people themselves believe that their ancestors came from Pagaruyung, West Sumatra Province. The purpose of this research is to determine the genetic variation and genetic distance of the Sakai tribe in Riau Province and the Minangkabau tribe in Pagaruyung Village, West Sumatra Province based on three microsatellite DNA loci (D2S1338, D16S539, and D13S317). A total of 10 alleles were found in three microsatellite loci of the Sakai tribe and 11 alleles in the Minangkabau tribe.  Data analysis using GenAlex 6.503 software showed that the heterozygous value of the Sakai and Minangkabau tribes was moderate with a value of 0.557 ± 0.062 in the Sakai tribe and 0.615 ± 0.073 in the Minangkabau tribe. Meanwhile, the value of genetic differentiation (F’ ST ) in these two tribes shows moderate genetic differences (0.088 ± 0.039). Genetically, Sakai people and Minangkabau tribes have similarities based on the D2S1338, D16S539, and D13S317 microsatellite DNA loci with a genetic distance of 0.269 and the proportion of identical genes (Genetic identity) of 0.764. This result is supported by alleles outflow or entry in the Sakai and Minangkabau tribes with a migration rate is four people per generation.